2021
DOI: 10.1002/adfm.202107360
|View full text |Cite
|
Sign up to set email alerts
|

Modulus‐Tailorable, Stretchable, and Biocompatible Carbonene Fiber for Adaptive Neural Electrode

Abstract: The extraneural electrodes that cling to the nerve show great advantages in decreasing the damage of nerves, as compared to the intraneural electrodes. The grand challenge for the extraneural electrode is the instability of its electrode–nerve interface during nerve movement. In the proposed research, an adaptive, stretchable, and biocompatible carbonene extraneural electrode, which integrates rigid 2D defective graphene nanosheets on the soft carbon nanotube (CNT) fiber, is designed. The rigid nanosheets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…As depicted in Figure g, a unique (200) crystal plane with 0.58 nm interplanar spacing was marked in the high-resolution TEM (HRTEM) image. , Furthermore, it is of interest to note that the (200) plane is parallel to the nanoribbon long axis direction, suggesting the preferred growth direction of this nanosheet. This special structure agrees very well with the previous reported results and could facilitate the chemical intercalation of metal ion charge carriers. , The TEM-EDX mapping shown in Figure h and i also illustrates the presence of evenly distributed V and O elements.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As depicted in Figure g, a unique (200) crystal plane with 0.58 nm interplanar spacing was marked in the high-resolution TEM (HRTEM) image. , Furthermore, it is of interest to note that the (200) plane is parallel to the nanoribbon long axis direction, suggesting the preferred growth direction of this nanosheet. This special structure agrees very well with the previous reported results and could facilitate the chemical intercalation of metal ion charge carriers. , The TEM-EDX mapping shown in Figure h and i also illustrates the presence of evenly distributed V and O elements.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Identical shapes and increasing current intensity of VO 2 /CCotton CV curves were gained, as the sweep rates increased from 1 to 5 mV s –1 , and are recorded in Figure b. It is worth noting the appearance of three pairs of redox peaks of VO 2 /CCotton in the CV plots, ascribing to stepwise solid-solution reactions during the representative reactions of the intercalation/extraction of Zn 2+ ion guests into/from the VO 2 host during the discharge/charge process. ,,, The power-law formula (eq ) reveals the relationship between the peak current intensity ( I p ) and the scan rate ( v ) as well as electrochemical reaction kinetics: where a and b here represent changeable parameters. In particular, the b value size indicates if the electrode material has pseudocapacitive behavior or not during charge and discharge processes. ,, As such, linear relationship plots of log­( I ) versus log­( v ) were obtained in Figure c.…”
Section: Results and Discussionmentioning
confidence: 88%
“…The bending stiffness of the CNT fiber was close to those of the biological tissues, which indicated that it could mechanically match soft tissues and thus establish a stable device/tissue interface. [30,31,34] To obtain the dynamic interface between fiber BFC electrode and the mouse brain under deformation, a fiber BFC electrode was implanted into the mouse brain, and photoacoustic (PA) images were collected before and after a compression was applied to the brain (Figure 4a). It indicated that the fiber electrode bent along with the compression deformation of the mouse brain, and achieved a stable device/ tissue interface.…”
Section: Resultsmentioning
confidence: 99%
“…In this manuscript, we report a flexible and anti-biofouling fiber BFC that can work in the brain with stable power output in the long term. The fiber BFC is constructed based on an intrinsic flexible carbon nanotube (CNT) fiber electrode, which is biocompatible [29,30] and mechanically match with soft biological tissues, [30,31] and thus commonly used for fabricating neural probes [32,33] and implantable electrochemical sensor. [30,34,35] The simple in situ polymerized hydrophilic zwitterionic polydopamine-2-methacryloyloxyethyl phosphorylcholine (PDA-MPC) layer modified on fiber BFC enables its resistance to nonspecific protein adsorption and maintenance of power output in complex biological fluids.…”
mentioning
confidence: 99%
“…Because of the large specific surface area and unique electrical, thermal, and optical properties of carbonene materials, functional carbonene fibers are widely applied in energy storage and conversion electronics (supercapacitors, batterie,s and nanogenerators), sensors, optoelectronic devices, neural recording systems, etc. , The intrinsic mechanical characteristics of carbonene materials ensure the flexibility of these fiber-shaped devices and allow them to be easily integrated with fabrics to produce wearable electronics. For intelligent applications, carbonene fibers are able to conduct actuation, thermal management, and color changing and undergo smart reactions under a stimulus. ,, A carbonene-modified fiber textile with a thin layer of CNTs on the surface of triacetate-cellulose bimorph fibers can modulate infrared radiation as the relative humidity of the underlying skin changes.…”
mentioning
confidence: 99%